Awareness of the industrialized building system (IBS) implementation in Northern Malaysia - A case study in Perlis - Kassim, Umar; Walid, Luqman (Elsevier Ltd., 2013)
The Industrialized Building Systems (IBS) can be defined in which all building components such as the wall, slab, beam, column and staircase are mass-produced either in the factory or on the factory site under strict quality control and minimal wet site activities (Warswaski, 1999). This research aims at looking into the current awareness of the IBS usage and its exposure method to the relevant population in Perlis, Malaysia. A total of 100 questionnaires were handed out to several parties, namely the Officer's Contractors’ Association of Malaysia (20), Public Works Department (PWD) Perlis (20), Repository Development Officer at River Chuchuh, Perlis (10), Lecturers, Engineering students (25) and the public (25). From the methods, 80% respondents have demonstrated an extent of general knowledge about this system. Meanwhile, 40% know about this system in great detail. Gradually, more respondents agree on the implementation of this system taking place in Perlis.Developers are under the impression that the implementation of the IBS is accompanied by high costs.As the conclusion, profound awareness of the benefits of using the IBS system is pivotal, as this technique is able to function effectively in the competition-based construction industry today.